The effects of the number of participants on collaborative l2 summary writing / Sri Darshini Bala Krishanan - Sri Darshini , Bala Krishanan (2018)
This study investigates the relationships between the number of participants in summary writing and the quality of their final summary writing. A total of 52 participants aged 16, participated in this four week, mixed-method study. The summaries were scored using Brown and Bailey’s (1984) scoring scale which has five components. The components are organization, logical development of idea, grammar, punctuation, spelling, mechanics and finally style and quality of expression. The participants’ overall scores and analytic scores were analysed with paired t-test (individual and collaborative group) and independent t-test (pair and groups of four). The paired t-test was utilized to compare the quality of summary writing by individual and collaborative groups. The results for the overall scores revealed that the collaborative writing improves students’ final summary writing and the analytic scoring revealed that the participants in the collaborative groups had improved in terms of organization, content, and grammar, whereas there was no improvements in terms of their punctuation, spelling, mechanics and style and quality of expressions components. On the other hand, the independent t-test was utilized to compare the performance of pairs and groups of four. The results for the overall score did not reveal any significant improvement, however there were improvements shown by groups of four in the mean score value. In contrast, the analytic scoring results revealed that the participants in groups of four had improved in all five components. This shows that working in groups of four helps participants’ to improve their summary writing compared to working in pairs as they can pool their knowledge and ideas better. The study also elicits participants’ feedback on collaborative summary writing. A questionnaire (Fernandez Dobao & Blum, 2012) was utilized to get their feedback. Majority reacted positively and agreed that collaborative task had improved their vocabulary knowledge compared to grammar and content. Thus, it reveals that collaborative writing helps the participants in improving their final writing through discussion as they get to learn from their partners. In future research, the sample size of the study should be expanded as the current study had only 52 participants. In addition, verbal interviews and Language Related Episodes (LREs) could be incorporated to obtain richer results. Finally, the participants could be selected based on the same proficiency level and the treatment phase could be extended.